Henri Lefebvre and the Spanish urban experience : reading the mobile city - Fraser, Benjamin (Bucknell University Press, with The Rowman & Littlefield Pub. Group, 2011)
An important contribution to the still evolving field of 'urban cultural studies, ' Henri Lefebvre and the Spanish Urban Experience is the first book to thoroughly apply the French urban philosopher's thoughts on cities to the culture and literatureof Spain. Fraser shows how Lefebvre's complex view of the city as a mobile phenomenon is relevant to understanding a variety of Spanish cultural products--from urban plans and short writings on the urban experience during the ninetheenth century by MarianoJosé de Larra, Ramón de Mesonero Ramanos, and Ildefons Cerdà to urban theories, cultural practice.